Enhanced Medial Prefrontal Cortex and Hippocampal Activity Improves Memory Generalization in APP/PS1 Mice: A Multimodal Animal MRI Study - Liu, Weilin; Li, Jianhong; Li, Le; Zhang, Yuhao; Yang, Minguang; Liang, Shengxiang; Li, Long; Dai, Yaling; Chen, Lewen; Jia, Weiwei; He, Xiaojun; Lin, Huawei; et al. (Frontiers in Cellular Neuroscience, 2022)
Memory generalization allows individual to extend previously learned movement patterns to similar environments, contributing to cognitive flexibility. In Alzheimer’s disease (AD), the disturbance of generalization is responsible for the deficits of episodic memory, causing AD patients to forget or misplace things, even lose track of the way home. Cognitive training can effectively improve the cognition of AD patients through changing thinking mode and memory flexibility. Here, a T-shaped maze was utilized to simulate cognitive training in APP/PS1 mice to elucidate the potential mechanisms of beneficial effects after cognitive training. We found that cognitive training conducted by T-shaped maze for 4 weeks can improve memory generalization ability of APP/PS1 mice. The results of functional magnetic resonance imaging (fMRI) showed that the functional activity of medial prefrontal cortex (mPFC) and hippocampus were enhanced after cognitive training. And the results of magnetic resonance spectroscopy (MRS) showed that the neurochemical metabolism of N-acetyl aspartate (NAA) and glutamic acid (Glu) in mPFC, hippocampus and reuniens thalamic nucleus of thalamus (Re) were all escalated. Furthermore, the functional activity of mPFC and hippocampus was negatively correlated with the escape latency tested in memory generalization. Therefore, these results suggested that cognitive training can improve memory generalization through enhancing the functional activity of mPFC and hippocampus and increasing the metabolism of NAA and Glu in the brain regions of mPFC, hippocampus and Re nucleus.